2022
DOI: 10.1097/tp.0000000000004398
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally Distinct B Cells Infiltrate Allografts After Kidney Transplantation

Abstract: Background. Following allogeneic kidney transplantation, a substantial proportion of graft loss is attributed to the formation of donor-specific antibodies and antibody-mediated rejection. B cells infiltrate kidney grafts during antibody-mediated rejection; however, the origins, repertoires, and functions of these intrarenal B cells remain elusive. Methods. Here, we use murine allogeneic kidney transplant models to study the origins, transcriptional programming and B cell receptor repertoire of intragraft B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“… 67 Evidence that B-cell maturation occurs in PT-TLOs is apparent from the minimal overlap of B-cell alloantibody repertoires in human kidney grafts and peripheral blood 38 and the fact that B-cell clones in TLOs of rejecting human kidneys exhibit somatic mutations and differ from those in peripheral blood, 67 consistent with similar earlier studies of TLOs in transgenic models 41 , 64 and autoimmunity. 65 , 66 Nevertheless, the absence of defined dark and light zones typical of SLOs, the generation of autoantibodies, 1 and an apparent defect in the ability to expand Tfh cells in rejecting kidney lymphoid infiltrates 68 suggest that, although events typical of SLO GCs occur in TLOs, some differences exist.…”
Section: Functions Of Pt-tlosmentioning
confidence: 99%
“… 67 Evidence that B-cell maturation occurs in PT-TLOs is apparent from the minimal overlap of B-cell alloantibody repertoires in human kidney grafts and peripheral blood 38 and the fact that B-cell clones in TLOs of rejecting human kidneys exhibit somatic mutations and differ from those in peripheral blood, 67 consistent with similar earlier studies of TLOs in transgenic models 41 , 64 and autoimmunity. 65 , 66 Nevertheless, the absence of defined dark and light zones typical of SLOs, the generation of autoantibodies, 1 and an apparent defect in the ability to expand Tfh cells in rejecting kidney lymphoid infiltrates 68 suggest that, although events typical of SLO GCs occur in TLOs, some differences exist.…”
Section: Functions Of Pt-tlosmentioning
confidence: 99%
“…54 In-depth analysis of histological features surrounding rejection would define the underlying immune–endothelial–epithelial–stromal interactions that contribute to damage, for example identifying how B-cell infiltrates or innate-like B cells may be retained, activated, or expanded in the cardiac and renal allografts. 55-57 Understanding these cellular interactions could lend insight into the development and nature of subclinical and borderline rejection episodes, of specific acute and chronic histological features, and of the contributions of donor and recipient immune cells to injury. 58-60…”
Section: Opportunities For Spatial Transcriptomics In Transplantation...mentioning
confidence: 99%
“…54 In-depth analysis of histological features surrounding rejection would define the underlying immune-endothelial-epithelial-stromal interactions that contribute to damage, for example identifying how B-cell infiltrates or innate-like B cells may be retained, activated, or expanded in the cardiac and renal allografts. [55][56][57] Understanding these cellular interactions could lend insight into the development and nature of subclinical and borderline rejection episodes, of specific acute and chronic histological features, and of the contributions of donor and recipient immune cells to injury. [58][59][60] In parallel to rejection, the high-resolution spatial analysis of tolerance and operational tolerance may reveal novel pathways to exploit therapeutically, for example, of regulatory lymphoid structures that can promote kidney allograft tolerance 61 or bronchus-associated lymphoid tissues from tolerant lung grafts that can promote peripheral tolerance.…”
Section: Opportunities For Spatial Transcriptomics In Transplantation...mentioning
confidence: 99%
“…[16][17][18] Recent studies found that infiltrating B-cell populations in rejecting hearts and kidneys are responsive to innate stimuli and have self-reactivity. 6,7,19,20 In this study, we sought to understand the differentiation of B cells after exposure to allogeneic antigen by tracking antigen-specific B cells after sensitization. We found that MZ B cells are critical for the formation of GC B cells and anti-donor IgG and thus represent an enriched reservoir of alloreactive B cells.…”
Section: Introductionmentioning
confidence: 99%